Land tenure security and land-cover change: a case study from protected area buffer zone communities in Madagascar - Chang, Stephen, author; Leisz, Stephen J., advisor; Galvin, Kathleen, committee member; Ojima, Dennis, committee member (Colorado State University. Libraries, 2023)
Tenure and property rights define the relationship that people have with land and natural resources. Customary tenure systems are predominant in Madagascar, where locally administered rule systems have the flexibility to adapt to changing conditions, inherent conflict resolution mechanisms, and often, community buy-in. However, laws and regulations at different governmental levels throughout the country's history have often caused tenure systems to overlap in rural areas, which, in turn, often causes conflict and tenure insecurity. One important alteration to existing land and natural resource tenure systems is the creation of protected areas, which are commonly created to preserve the endemic biodiversity of the country. Many investigations have attempted to link land tenure to land-cover change using earth observing satellite imagery, but the study reported here is the first of the kind for Madagascar. This study addresses the following questions: if and how a land tenure system and its relative security influence land-cover change within a community and if and how land tenure outside of a protected area influences change within. Land cover classifications created from the Landsat TM and ETM+ images achieved high accuracies despite low image availability due to the period during which the study took place and the significant cloud cover found over the study sites. Findings of the study show that protected areas are relatively unaffected by surrounding land-use and land tenure security in the villages near the protected areas, and that the protected areas are effective at conserving the forests within their boundaries. Within each community, however, conflict and tenure insecurity are associated with elevated conversion of forest areas to other land-covers, regardless of tenure. These results highlight the need to prioritize land tenure security to both ensure local communities access to land and natural resources and meet widespread goals related to conserving biodiversity held by the international conservation community through the support of customary tenure systems and the promotion of socially responsible agricultural transitions.
Keywords: land tenure; remote sensing; land tenure security; land cover change